Comparison of the quality of life before and after septorhinoplasty - İhvan, Önder; Cingi, Cemal; Kezban Gürbüz, Melek; Özüdoğru, Erkan; Çaklı, Hamdi; İncesulu, Armağan; Keçik, Cem (ENT Updates, 2012)
Objective: The aim of our study is to assess the impact of septorhinoplasty on quality of life (QOL) using general health and disease-specific quality scales and to identify the effect of age, gender and education on the change process of the patient's quality of life. Methods: The study included patients with septal deviation and external nasal deformity. Short Form 36 and Esthetic Functional Nasal Assessment Form (EFBDF) were used as QOL instruments; and rhinomanometry to measure airway resistance. Tests were conducted just before surgery and three months and one year after surgery. Results: Forty-one patients (22 males, 19 females, mean age 29.9) undergoing nasal surgery were studied prospectively. Compared to preoperative scores, we found significant improvements in general health, mental health, energy, pain, physical and social function scores of SF-36 subscales conducted in the third month and first year after the surgery. There was no difference in physical role and emotional role subscales. Nasal surgery specific EFBDF scores were significantly improved in two measurement periods following surgery compared to preoperative values. The pre/post-operative rhinomanometric measurements showed an improvement and the difference was also significant. There was no correlation between QOL instruments with sex, age and educational status. Conclusion: Our study has shown that general and nasal specific QOL was improved with SRP patients assuming that correct indication for surgery is given and correct surgical method is chosen. Also SRP patients were able to breathe more efficiently through their noses after surgery.